Accounting students' perceptions of important business communication skills for career success: An exploratory study in the Tunisian context. Issue 2 (3rd July 2017) - Oussii, Ahmed Atef; Klibi, Mohamed Faker
Abstract : Purpose: This paper aims to examine the business communication skills that accounting students see as having the highest importance for career success. It also explores the current levels of development of these skills and analyzes them through a comparative study between three Tunisian business schools. Design/methodology/approach: The authors used a questionnaire sent to180 students from three business schools to provide insights into the development of communication skills perceived important for a successful accounting career. Findings: The results indicate that all students are conscious of the importance held by communication skills for career success in the accounting profession. However, they feel that their aptitudes are sometimes poorly developed, especially when it comes to proficiency in French (as a language of business in Tunisia) and written skills. Practical implications: The paper's findings offer important guidance concerning the communication skills that accounting students consider most needed by the Tunisian labor market. The findings of this study may be useful for curriculum development in local and international contexts. Originality/value: This study is conducted in a developing country where the graduate unemployment rate is about 30 per cent. This high unemployment often affects service professions like accounting. Moreover, in Tunisia, accounting education focuses particularly on technical aspects. So far, no studies have been conducted to show whether students nowadays are aware of the increasing importance of generic skills in accounting practice. As a result, the conclusions of this study could provide Tunisian stakeholders with insights into ways of potentially improving accounting graduates' employability.